2014
DOI: 10.1586/14737159.2015.993612
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic profile on the IFA 40: HEp-20-10 – an immunofluorescence test for reliable antinuclear antibody screening

Abstract: Indirect immunofluorescence assay is the recommended gold standard to test for antinuclear antibodies (ANA), which are important biomarkers for systemic rheumatic autoimmune diseases. It is internationally accepted that indirect immunofluorescence assay ANA screening is most sensitive on human epithelial (HEp-2) cells. The cells present a multitude of antigens that display distinguishable localization patterns in interphase and mitotic cells in indirect immunofluorescence analysis. Here, we present the IFA 40:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…Of note, the analytical performance of HEp-2 IIF crucially depends on the quality of the substrate and assay, particularly with regard to the ratio of mitotic versus interphase cells, cell morphology, reproducibility, and dilution linearity. The HEp-20-10 substrate (a variant of the standard HEp-2 cell line with a 10-fold higher number of mitotic cells), as used in the present study, has been reported to facilitate the recognition, discrimination and titer estimation of ANA patterns ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the analytical performance of HEp-2 IIF crucially depends on the quality of the substrate and assay, particularly with regard to the ratio of mitotic versus interphase cells, cell morphology, reproducibility, and dilution linearity. The HEp-20-10 substrate (a variant of the standard HEp-2 cell line with a 10-fold higher number of mitotic cells), as used in the present study, has been reported to facilitate the recognition, discrimination and titer estimation of ANA patterns ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…Constant quality of the substrate is ensured by quality control measures throughout the production of the HEp-20-10-coated biochips. Reliability of the assay has been demonstrated by validation studies ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Samples and slides were processed using the Sprinter XL (Euroimmun AG, Lübeck, Germany), followed by automated evaluation using the EUROPattern Suite (Euroimmun AG, Lübeck, Germany). ANA detection was performed by the IFA 40: HEp-20-10 kit assay according to the manufacturer’s instructions (Euroimmun AG, Lübeck, Germany) ( 57 ). The IFA 40: HEp-20-10 allows for easier evaluation due to an increased spectrum of cells in the mitotic phase and of human nuclear antigens when compared to traditional Hep-2 cells.…”
Section: Methodsmentioning
confidence: 99%
“…Monkey liver tissue is helpful to determine fluorescence patterns, especially in some undistinguishable patterns. The fluorescence characteristics in monkey liver tissue are key points of identification, thus avoiding mistakes ( 23 , 24 ). In the first incubation step, specific antibodies from the diluted patient sample bind to the solid-phase bound antigens.…”
Section: Methodsmentioning
confidence: 99%